For x ≥ 0, the value of h(k(x)) is not equal to the value of k(h(x)).
For x ≥ 0, h and k are not inverse function.
In Mathematics, two functions will reverse the effect on each other if the two functions are inverses. This ultimately implies that, if h(x) and k(x) are functions and (h∘k)(x) = x, and (k∘h)(x) = x, then h(x) and k(x) are considered inverses of one another.
By substituting the function k(x) into the function h(x), the corresponding composite function h(k(x)) can be calculated as follows;
![h(k(x))=5(√(5x+1) )^(2) -1\\\\h(k(x))=5(5x+1)-1\\\\h(k(x))=25x+5-1\\\\h(k(x))=25x+4\\\\h(k(1))=25(1)+4\\\\h(k(1))=29](https://img.qammunity.org/2023/formulas/mathematics/college/a0e1eowjxzup0sx0oilo766hfb0eaydju9.png)
By substituting the function h(x) into the function k(x), the corresponding composite function k(h(x)) can be calculated as follows;
![k(h(x))=√(5(5x^2 - 1)+1) \\\\k(h(x))=√(25x^2 - 5+1)\\\\k(h(x))=√(25x^2 - 4)\\\\k(h(1))=√(25(1)^2 - 4)\\\\k(h(1))=√(21)](https://img.qammunity.org/2023/formulas/mathematics/college/pd13s6xsp9qo71e293zs5942yosbqutv7v.png)
Since the output value for each composite function are not the same, we can logically deduce that the functions h(x) and k(x) are not inverse functions;
h(k(x)) ≠ k(h(x)), for x ≥ 0.